Política migratoria: entre el discurso, la práctica y la coyuntura - Durand Arp-Nisen, Jorge (El Colegio de México A.C., 2019)
In this text we will evaluate the general approaches taken by migration policy during the presidency of President Enrique Peña Nieto, as embodied in the Special Migration Program, and in the manner in which it was put into practice by the officials in charge. Finally, the most representative cases will be analyzed: the creation of the Southern Border Plan in response to the humanitarian crisis of migrant children and families, the diversion of funds from the IME to Juntos Podemos, and the Honduran caravans at the end of the six-year period.